Botulinum Toxin Type A for Lumbar Sympathetic Ganglion Block in Complex Regional Pain Syndrome: A Randomized Trial. (February 2022) - Yoo, Yongjae; Lee, Chang-Soon; Kim, Jungsoo; Jo, Dongwon; Moon, Jee Youn
Abstract : Background: The present study was designed to test the hypothesis that botulinum toxin would prolong the duration of a lumbar sympathetic block measured through a sustained increase in skin temperature. The authors performed a randomized, double-blind, controlled trial to investigate the clinical outcome of botulinum toxin type A for lumbar sympathetic ganglion block in patients with complex regional pain syndrome. Methods: Lumbar sympathetic ganglion block was conducted in patients with lower-extremity complex regional pain syndrome using 75 IU of botulinum toxin type A (botulinum toxin group) and local anesthetic (control group). The primary outcome was the change in the relative temperature difference on the blocked sole compared with the contralateral sole at 1 postoperative month. The secondary outcomes were the 3-month changes in relative temperature differences, as well as the pain intensity changes. Results: A total of 48 participants (N = 24/group) were randomly assigned. The change in relative temperature increase was higher in the botulinum toxin group than in the control group (1.0°C ± 1.3 vs. 0.1°C ± 0.8, respectively; difference: 0.9°C [95% CI, 0.3 to 1.5]; P = 0.006), which was maintained at 3 months (1.1°C ± 0.8 vs. –0.2°C ± 1.2, respectively; P = 0.009). Moreover, pain intensity was greatly reduced in the botulinum toxin group compared with the control group at 1 month (–2.2 ± 1.0 vs. –1.0 ± 1.6, respectively; P = 0.003) and 3 months (–2.0 ± 1.0 vs. –0.6 ± 1.6, respectively; P = 0.003). There were no severe adverse events pertinent to botulinum toxin injection. Conclusions: In patients with complex regional pain syndrome, lumbar sympathetic ganglion block using botulinum toxin type A increased the temperature of the affected foot for 3 months and also reduced the pain. Abstract : Lumbar sympathetic ganglion block with botulinum toxin type A caused a greater increase in temperature in the blocked limb at 1 month than did levobupivacaine. Botulinum toxin administration also provided better analgesia at 1 and 3 months after injection than did levobupivacaine, while no adverse events were observed.Supplemental Digital Content is available in the text.